Effect of the Mo Structure on CIGS Solar Cells Fabricated on Stainless Steel Substrates. Issue 10 (24th August 2015) - Kim, Deok‐In; Kim, Kyoung‐Bo; Kim, Moojin; Jeon, Chan‐Wook
Abstract This study examined the effects of the bilayer structure of a Mo back contact and its total thickness on the diffusion behavior of substrate impurities, as well as the performance of CdS/Cu(In, Ga)Se2/Mo/stainless steel solar cells. The thick Mo, with a total thickness of 1.0 μm and a low density region of 0.2 μm, resulted in poorer photoconversion efficiency than the thin Mo with a total thickness of 0.5 μm and a low density region of 0.1 μm. The efficiency loss was attributed to deterioration of the quantum efficiency and diffusion length due to increased Fe contamination. This suggests that the saturation of Cr near the interface between the high density region and the low density region in the Mo bilayers, which was favored in the 0.5 μm thick Mo layer with thinner low density region, provided a self‐diffusion barrier against the further diffusion of Fe.